A Narrative Review on the Bioactivity and Health Benefits of Alpha-Phellandrene - Subramanian Thangaleela; Bhagavathi Sundaram Sivamaruthi; Periyanaina Kesika; Tanawat Tiyajamorn; Muruganantham Bharathi; Chaiyavat Chaiyasut (MDPI AG, 2022)
Aromatic essential oils play a significant role in pharmaceuticals, food additives, cosmetics, and perfumery. Essential oils mostly comprise aliphatic hydrocarbons, monoterpenoids, sesquiterpenoids and diterpenes. Plant extracts comprise a complex mixture of terpenes, terpenoids, aliphatic and phenol-derived aromatic components. Terpenes are a significant class of hydrocarbons with numerous health benefits. These biological functions of essential oil components are examined in vitro and in vivo studies. Some studies evaluated the properties and functions of α-phellandrene (α-PHE). Detailed evaluation to determine the functions of α-PHE over a spectrum of health care domains needs to be initiated. Its possible mechanism of action in a biological system could reveal the future opportunities and challenges in using α-PHE as a pharmaceutical candidate. The biological functions of α-PHE are reported, including anti-microbial, insecticidal, anti-inflammatory, anti-cancer, wound healing, analgesic, and neuronal responses. The present narrative review summarizes the synthesis, biotransformation, atmospheric emission, properties, and biological activities of α-PHE. The literature review suggests that extended pre-clinical studies are necessary to develop α-PHE-based adjuvant therapeutic approaches.